L'accent orientatif - Vitez, Primož (Vestnik za tuje jezike, 2015)
The history of describing the French final accent - and French accentuation in general - is fulfilled by different and very heterogenous approaches, analyzing this prosodic feature in French from both substantial and functional points of view. Viewed through pragmatical frame, the final accent is a) one of the key aspects in shaping the acoustical image of spoken French and b) a strategic tool for the speaker to build the coherence and sense of uttering. The distribution of final accents, i. e. forming accentual units, helps the speaker and his adressee to form a refined strategy in generating and perceiving the spoken text. From the discourse point of view it is therefore justified to define the French final accent as an orientational prosodic feature.
Keywords: francoščina; French; naglas; naglaševanje; terminologija; terminology; prozodija